NUCLEOLUS ORGANIZER REGION (NOR) BANDING IN MAHABUBNAGAR LOCAL GOATS - P. Uma Devi; B. Ramesh Gupta; K. Sakunthala Devi (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Nucleolus organizer regions (NORs) on the chromosomes of Mahabubnagar local goats were studied using shot-term lymphocyte culture technique. The ammoniacal silver staining procedure was followed with minor modifications . The chromosomes were stained with Silver-Giemsa staining technique using gelatin colloidal developer. The frequency distribution of number of metaphases containing the Ag-NOR bands were tested for significance by Chi-square test. A total of 213 NORs were detected in 42 metaphases. The mean number of NORs per metaphase was 5.071, with a range from 4.72 to 6.17, while the number of NORs per metaphase ranged from 1 to 13. Frequency of the metaphases reduced as the number of NORs per metaphase increased. The Chi-square test of significance has revealed that the observed frequencies departed significantly from the expected frequencies (P<0.05). The highest frequency of metaphases (21.43%) examined had one NOR, while the lowest frequency (2.38%) had 9 or 11 NORs. The chromosome morphology, number and morphometric measurements and NORs in Mahabubnagar local goats were similar to those of the descript breeds of goats in India.